Public Debt and Economic Growth – Economic Systems Matter - Markus Ahlborn; Rainer Schweickert (International Economics and Economic Policy, 2018)
Most studies on the relationship between public debt and economic growth implicitly assume homogeneous debt effects across their samples. We –in accordance with recent literature– challenge this view and state that there likely is a great deal of cross-country heterogeneity in that relationship. However, other than scholars assuming that all countries are different, we expect that clusters of countries differ. We identify three country clusters with distinct economic systems: Liberal (Anglo Saxon), Continental (Core EU members) and Nordic (Scandinavian). We argue that different degrees of fiscal uncertainty at comparable levels of public debt between those economic systems constitute a major source of heterogeneity in the debt-growth relationship. Our empirical evidence supports this assumption. Continental countries face more growth reducing public debt effects than especially Liberal countries. There, public debt apparently exerts neutral or even positive growth effects, while for Nordic countries a non-linear relationship is discovered, with negative debt effects kicking in at public debt values of around 60% of GDP.
Keywords: E62; P10; P51; H10; 330; public debt; economic growth; economic systems; fiscal policy; welfare state